Cultural Considerations in Biomedical Translations - Dr. Teibowei Marie Therese (Journal of Linguistics and Communication Studies, 2023)
Biomedical translations do not occupy the most central position in the world of medicine, it certainly plays an important role in knowledge mediation, which involves sharing medical research results, publicizing new findings in the international scientific community and marketing new medical products and services. This study explores the place of cultural consideration in biomedical translation in Nigeria. Conceptual clarification on culture, cultural considerations Biomedical translation was done. Cultural consideration in biomedical translation were discussed. Strategies for managing cultural considerations were highlighted. It was suggested amongst other that prospective medical expert should be encouraged to consider the differences cultures while consuming the products of Biomedical translations.